Dispositivo de gênero: padrões sociais de feminilidade e masculinidade em revistas brasileiras - Santana, Sarah Carime Braga (2024)
This thesis takes as its object of study the discourse practices that establish a binary relationship (femininities vs masculinities) that create and legitimate, through discourses, social and economic patterns that define ways of being a woman or a man in a given society, considering how the relationships of knowledge-power, operated by and by means of discourses, touch the relationships between genders and establish a pattern that focus on a cis-heteronormative matrix, that is, a social model that has, as its foundation, subjects that identify themselves with their biological gender, attributed to them when they were born, and who affirm themselves as heterosexual subjects. Based on this topic, we will discuss the gender device, and we will intend to discuss how this device is concretized when the discourse object encompasses heterosexual and homosexual subjects, who respectively correspond to a hegemonic and non-hegemonic pattern of exercise of femininities and masculinities. The discussion of such topics will be carried out referring to publications issued in magazines that circulate nationally, which, constitutively, dedicate themselves to topics regarding behavior, lifestyle, fashion and culture, that is, address daily life interests of their target public. For this, the selected corpus is comprised of three feminine magazines and two masculine magazines, the analytical excerpts were obtained from digital issues of the magazines Claudia, Marie Claire and Ana Maria, which present content for the feminine public, and the magazines GQ Brasil and L’Officiel Hommes Brasil, oriented to the masculine public, which were publicized between 2017 and 2023. Based on the establishment of a relationship between the subject, the object of knowledge and the representation itself of knowledge as a truth with which we operate the conceptual field, this work presents, as theoretical approach, the Foucauldian Discourse Studies, with focus on the discursive event and on reflections about subjectivity and knowledge-power relationships. In addition, we will resort to the gender theory brought about especially by Judith Butler, so that we may, with Foucault, think the constitution of a device, and with Butler, think the way the gender theory leads us, by means of discourses and the exercise of power, through behavior control, to the constitution of the gender device. Regarding the topic of gender that will be addressed, it comprises several propositions of a philosophic, religious, and mainly scientific nature, but which can be presented together due to their similarities. Meanwhile, the analyses developed from the clipping of non-linear enunciative series, which are found in a discursive dispersion, while at the same time they present a regularity in the objects they talk about, constituting an enunciative chain about the subject positions and the possible places to be socially performed by men and women. Upon considering the notes taken above, the central objective of this research may be summarized as the investigation and analysis of how the discursive practices that compose the analytical material define, from a gender device, the masculine and feminine social roles, objectify and subjectify subjects, limit their freedom, rule their bodies, promote interdictions and delimit the fields of performativity possible to the exercise of femininities and masculinities of the subjects. The results obtained indicate that the Gender Device has its emergence based on the production of discourses that maintain a cis-heteronormative gender hegemony, which rules the exercise of femininities and masculinities while defining the social roles possible to woman and man subjects.